2022
DOI: 10.2319/040921-290.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between stereophotogrammetry and smartphone structured light technology for three-dimensional face scanning

Abstract: Objectives To compare three-dimensional facial scans obtained by stereophotogrammetry with two different applications for smartphone supporting the TrueDepth system, a structured light technology. Materials and Methods Facial scans of 40 different subjects were acquired with three different systems. The 3dMDtrio Stereophotogrammetry System (3dMD, Atlanta, Ga) was compared with a smartphone (iPhone Xs; Apple, Cupertino, Calif)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…A conventional 2D cephalometric analysis using lateral and frontal cephalograms, along with facial scanning, is currently the main diagnostic imaging modality used for orthodontic diagnosis and treatment planning [17,18]. The main disadvantages of the 2D…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conventional 2D cephalometric analysis using lateral and frontal cephalograms, along with facial scanning, is currently the main diagnostic imaging modality used for orthodontic diagnosis and treatment planning [17,18]. The main disadvantages of the 2D…”
Section: Discussionmentioning
confidence: 99%
“…A conventional 2D cephalometric analysis using lateral and frontal cephalograms, along with facial scanning, is currently the main diagnostic imaging modality used for orthodontic diagnosis and treatment planning [17,18]. The main disadvantages of the 2D conventional cephalometry are represented by projective displacement, rotational errors, and linear projective transformation, which might affect the reliability and reproducibility of the relevant measurements [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that the Bellus3D application compared well with more expensive devices for face scanning in terms of accuracy [ 22 , 23 , 24 , 25 ]. Although the Bellus3D application has been made unavailable for download since 1 December 2021, several other systems are currently available for 3D face scanning [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…3D stereophotogrammetry and 3D scanning of the oral cavity were used in order to obtain an accurate evaluation without exposing patients to radiation [ 26 ]. The .stl files of the face were acquired with stereophotogrammetry (3dMDtrio System; 3dMD, Atlanta, GE, USA), considered the gold standard for stereophotogrammetry [ 27 ], and were then processed using the Geomagic 2014 (64 bit) software. To delineate the most peculiar facial signs of Crouzon syndrome, the following linear and surface measurements were carried out: surface measurement of eyeball protrusion (EBP) and linear measurement of inner intercanthal distance (ICD).…”
Section: Methodsmentioning
confidence: 99%